2014
DOI: 10.4103/0973-029x.151357
|View full text |Cite
|
Sign up to set email alerts
|

Chondroblastic osteosarcoma

Abstract: The purpose of this paper is to report a case of chondroblastic osteosarcoma in the region of the maxilla, with 5 months of evolution. The term osteosarcoma refers to a heterogeneous group of malignancies with bone formation or mesenchymal tissue with histopathological evidence of osteogenic differentiation. The pattern of chondroblastic osteosarcoma represents 25% of all reported cases of this neoplasm. Its histopathological diagnosis is based on the predominance of a chondroid matrix formed in the midst of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…It is important to note that there were malignant osteoblastic cells in the chondroblastic OS lesions based on H&E staining examination, which were further supported by the scRNA-seq that the cells expressing both COL1A1 and SOX9 were identified in the chondroblastic OS lesions BC20 and BC22. Previous study suggested that chondrocytes could undergo a direct transdifferentiation process into osteoblasts during the endochondral ossification in bone formation 70 . With the CNV clonal analysis by inferCNV with the scRNA-seq revealed a large scale genomic copy message, we found a great portion of genomic CNV pattern shared between the chondroblastic and osteoblastic malignant subclones in chondroblastic OS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that there were malignant osteoblastic cells in the chondroblastic OS lesions based on H&E staining examination, which were further supported by the scRNA-seq that the cells expressing both COL1A1 and SOX9 were identified in the chondroblastic OS lesions BC20 and BC22. Previous study suggested that chondrocytes could undergo a direct transdifferentiation process into osteoblasts during the endochondral ossification in bone formation 70 . With the CNV clonal analysis by inferCNV with the scRNA-seq revealed a large scale genomic copy message, we found a great portion of genomic CNV pattern shared between the chondroblastic and osteoblastic malignant subclones in chondroblastic OS lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The resection with tumor-free margins and systemic chemotherapy are the standard treatment option. [ 3 , 7 , 21 , 22 ] Osteosarcoma is quite resistant to radiotherapy. However, in special locations where surgery is not feasible or for cases of bone metastases or in multifocal osteosarcoma, radiotherapy can prolong survival, and decrease pain intensity.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 – 6 ] It is characterized by predominant presence of chondroid matrix, which tends to exhibit a high degree of hyaline cartilage and is intimately associated with the non-chondroid element (osteoid or bone matrix). [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Chondroblastic osteosarcoma represents approximately 25% of all osteosarcoma diagnoses, and its diagnosis is based on the predominance of a chondroid matrix within the neoplastic cells. 2 Patients diagnosed with osteosarcoma typically present with pain and swelling, and the diagnosis can be easily delayed due to other suspected and much more benign disease processes such as trauma, arthritis, or growing pains. 3 Osteosarcoma is typically graded as low grade, high grade, or metastatic.…”
Section: Introductionmentioning
confidence: 99%